Creativity And Performance Of Women Entrepreneurs: The Moderating Role Of Family Support - Priambodo, Aji; Metris, Diksi (Value : Jurnal Manajemen dan Akuntansi, 2024)
Given the significant role these businesses play in economic development and the unique challenges faced by women entrepreneurs, the entrepreneurial performance of women in micro-, small-, and medium-sized enterprises (MSMEs). This study investigated the influence of expertise, creative thinking skills, and motivation on the performance of female entrepreneurs in MSMEs. Additionally, it examined the moderating effect of family support on these relationships. A quantitative approach was adopted, utilizing a survey methodology with a 5-point Likert scale questionnaire administered to 152 female entrepreneurs operating MSMEs. Data analysis was conducted using structural equation modeling techniques with SmartPLS software. The results indicate that expertise, creative thinking skills, and motivation positively affect the performance outcomes of women entrepreneurs. Furthermore, family support significantly moderated these relationships, strengthening the impact of expertise, creative thinking abilities, and motivation on entrepreneurial performance. This study contributes to the literature by providing novel insights into the role of family support in enhancing the relationship between creativity and entrepreneurial performance in women-owned MSMEs. These findings underscore the critical importance of fostering creativity, promoting motivation, and leveraging family support to improve women's entrepreneurial success in the MSME sector.